2013
DOI: 10.1080/15532739.2014.890090
|View full text |Cite
|
Sign up to set email alerts
|

Access to HIV Care and Support Services for African American Transwomen Living with HIV

Abstract: Low access to HIV care and support has led to survival rates for transwomen that are half that of other populations at risk for HIV. Within the population, HIV disproportionately impacts African American transwomen. Interventions to increase access to HIV care and support are needed to better serve those most affected and vulnerable within the population. We conducted a study of barriers and facilitators to care and support services for African American transwomen to fill a gap in the literature to improve acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
60
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 59 publications
(64 citation statements)
references
References 24 publications
1
60
1
1
Order By: Relevance
“…However, few (12%) transwomen in our study had access to trans-specific healthcare, and it is known that transwomen have significant challenges to accessing primary and HIV medical care, even where it is available [13,17,18]. Additionally, studies of transwomen living with HIV in the USA and Canada identified fear of disclosure of transgender identity, poor treatment by staff, and providers’ lack of awareness of transgender issues, as important barriers to engagement in care [19,20].…”
Section: Discussionmentioning
confidence: 99%
“…However, few (12%) transwomen in our study had access to trans-specific healthcare, and it is known that transwomen have significant challenges to accessing primary and HIV medical care, even where it is available [13,17,18]. Additionally, studies of transwomen living with HIV in the USA and Canada identified fear of disclosure of transgender identity, poor treatment by staff, and providers’ lack of awareness of transgender issues, as important barriers to engagement in care [19,20].…”
Section: Discussionmentioning
confidence: 99%
“…Other research experiences and input from community partners suggested that among some communities of color, transgender persons do not often socialize and interact with gay, bisexual, and other MSM, and thus it would not be possible to create an intervention that brings these communities together (Wilson, Arayasirikul, & Johnson, 2013). However, in this analysis, we found the opposite to be true; most events with transgender persons in attendance were hosted by the gay-identified male Navegantes.…”
Section: Discussionmentioning
confidence: 99%
“…34 Transwomen who are in a racial/minority group may be even more reluctant to attempt to access to care because of racial discrimination on top of that related to transgender identity. 35 Interesting findings arose between transwomen who were living with HIV and those who were not. Both has high utilization of hormones, but transwomen living with HIV had less utilization of genital surgery and breast augmentation.…”
Section: Discussionmentioning
confidence: 99%